ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMA NEGERI UNTUK STANDARISASI RPP DI KABUPATEN SIJUNJUNG - Fiantika, Suci; Risdawati, Renny; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTProfessional teachers are teachers who are able to develop learning tools such as the annual program, the semester program, syllabus and lesson plan (RPP). In this case the teachers are required to prove their professionalism to design the lesson plans. However, in general classroom teachers state high schools in district XI Sijunjung make lesson plan indicators relate to each other without regard to the purpose of learning. This study aims to find out standardization lesson plan made by biology teacher Class XI Semester II state high schools in district Sijunjung. This research is a descriptive study, with a view component completeness lesson plan and lesson plan analyze the relationship between the components. Samples taken by stratified random sampling. Of this study showed that in terms of the completeness of components obtained an average RPP for completeness existing lesson plan component is 63.13% with enough standard criteria, Â and 36.87% were not there with not standard criteria, and the average RPP made by high school biology teacher in class XI country in the district is 65.125% Sijunjung with fairly standard criteria. From the analysis it can be concluded that the lesson plans created by teachers biology classes in the District XI State high schools Sijunjung enough standard.